Sub-national non-bank finance: between the government of “particular zones” and the porous borders of the state - García Tarsia, Aldana (Universidad Nacional del Litoral, 2021)
This research addresses non-bank finance in subnational entities, questioning the financing mechanisms for productive activities deployed by vulnerable segments in the 2015-2021 period. Specifically, we analyse the cases of IADEP in the province of Neuquén, IDEP in Tucumán and Fuerza Solidaria in the province of Buenos Aires, a comparison of which has allowed us to build interpretations on the patterns observed in non-bank finance. The methodological approach employed is qualitative, using primary and secondary sources of information. Among the findings, we highlight the construction of a new subject of government emerging from the intersection between demands and offers, through which it is possible to glimpse the productive structure and the agendas of subnational government, in such a way that the relationships established between those who have access to different non-bank mechanisms and those who hold their government are central to the approach proposed here.